Hydrophilic PAMAM dendrimer grafted Janus membrane for oil-water emulsion separation - Yunqi Chen; Xiang Wang; Haoyuan Sun; Xinqiang Wang; Baihu Dong; Chaogang Fan; Yingfeng Tu; Shaohui Lin; Qinmin Pan; Xianshe Feng; Flora T.T. Ng (Journal of Environmental Chemical Engineering, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Membrane separation model integrated nanofiltration system for monovalent/divalent ion fractioning - Guozhong Shi; Yaqin Zhang; Hai Huang; Yingfeng Lai; Lin Zhang (Chemical Engineering Journal, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

Spatio-Temporal Dynamics of Particulate Organic Carbon and Its Response to Climate Change: Evidence of the East China Sea from 2003 to 2022 - Zhenghan Liu; Yingfeng Chen; Xiaofeng Lin; Wei Yang (Journal of Marine Science and Engineering, 2025)
Particulate organic carbon (POC) plays a crucial role in oceanic climate change. However, existing research is limited by several factors, including the scarcity of long-term data, extensive datasets, and a comprehensive understanding of POC dynamics. This study utilizes monthly average POC remote sensing data from the MODIS/AQUA satellite to analyze the spatiotemporal variations of POC in the East China Sea from 2003 to 2022. Employing correlation analysis, spatial autocorrelation models, and the Geodetector model, we explore responses to key influencing factors such as climatic elements. The results indicate that POC concentrations are higher in the western nearshore areas and lower in the eastern offshore regions of the East China Sea (ECS). Additionally, concentrations are observed to be lower in southern regions compared to northern ones. From 2003 to 2022, POC concentrations exhibited a fluctuating downward trend with an average annual concentration of 121.05 ± 4.57 mg/m3. Seasonally, monthly average POC concentrations ranged from 105.48 mg/m3 to 158.36 mg/m3; notably higher concentrations were recorded during spring while summer showed comparatively lower levels. Specifically, POC concentrations peaked in April before rapidly declining from May to June—reaching a minimum—and then gradually increasing again from June through December. Correlation analysis revealed significant influences on POC levels by particulate inorganic carbon (PIC), sea surface temperature (SST), chlorophyll (Chl), and photosynthetically active radiation (PAR). The Geodetector model further elucidated that these factors vary in their impact: Chl was identified as having the strongest influence (q = 0.84), followed by PIC (q = 0.75) and SST (q = 0.64) as primary influencing factors; PAR was recognized as a secondary factor with q = 0.30. This study provides new insights into marine carbon cycling dynamics within the context of climate change.

Exploring the effect of high pressure in the denaturation of casein micelles by in-situ SERS - Zhenhong Zheng; Han Lu; Yingfeng Lin; Lingling Shui; Mingliang Jin; Zhuo Jiang (Food Chemistry, 2024)

Comprehensive investigation of pressure-induced gelatinization of starches using in situ and ex-situ technical analyses - Yingfeng Lin; Xueshuang Yao; Sinan Zhang; Hengzhong Zhang; Zhuo Jiang (Food Chemistry, 2024)

The spatio-temporal characteristics of aerosol optical thickness as well as the relationship with PM2.5 in Xiamen city, China - Zhongyong Xiao; Xianquan Xie; Xiaofeng Lin; Jinghan Xie; Jiongfeng Chen; Yiqiang Shi; Yingfeng Chen (Environmental Monitoring and Assessment, 2020)

Isolation and Analysis of Salt Response of Lactobacillus plantarum FS5-5 from Dajiang - Xuefei Song; Qianqian Wang; Xin Xu; Jingwei Lin; Xiaorui Wang; Yating Xue; Rina Wu; Yingfeng An (Indian Journal of Microbiology, 2016)